2014
DOI: 10.1002/art.38744
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab With or Without a Conventional Maintenance Agent in the Treatment of Relapsing Granulomatosis With Polyangiitis (Wegener's): A Retrospective Single‐Center Study

Abstract: Objective. To evaluate the efficacy and safety of rituximab (RTX) induction therapy and the duration of remission, when RTX is used with or without a conventional maintenance agent, in a cohort of patients with granulomatosis with polyangiitis (Wegener's) (GPA).Methods. This was a retrospective, single-center study of patients with relapsing GPA treated with at least 1 course of RTX (4 weekly doses of 375 mg/m 2 intravenously [IV] or 2 fixed doses of 1,000 mg IV 2 weeks apart). Complete remission was defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
0
25
0
2
Order By: Relevance
“…gov Identifier: NCT 01697267) is evaluating rituximab, 1000 mg every 4 months (vs azathioprine), for maintenance in relapsing AN-CA-positive patients with GPA or MPA following a glucocorticoid-rituximab-based induction. Because none of these rituximab-based maintenance options have been validated and/or officially approved yet, the remaining choices following rituximab-based induction are, in practice, to retreat (with rituximab) only for clinical relapse or to give a conventional maintenance immunosuppressive agent such as azathioprine or methotrexate (92,98).…”
Section: Treatmentmentioning
confidence: 99%
“…gov Identifier: NCT 01697267) is evaluating rituximab, 1000 mg every 4 months (vs azathioprine), for maintenance in relapsing AN-CA-positive patients with GPA or MPA following a glucocorticoid-rituximab-based induction. Because none of these rituximab-based maintenance options have been validated and/or officially approved yet, the remaining choices following rituximab-based induction are, in practice, to retreat (with rituximab) only for clinical relapse or to give a conventional maintenance immunosuppressive agent such as azathioprine or methotrexate (92,98).…”
Section: Treatmentmentioning
confidence: 99%
“…However, relapses are frequent in patients treated with only rituximab (8). It was reported that routine re-treatment with rituximab alone, or in combination with azathioprine or MTX, was effective in preventing relapses (8,9). In our case, the induction therapy with rituximab and azathioprine with PSL 60 mg daily was ineffective, and resulted in the recurrence of OPN after a month.…”
Section: Discussionmentioning
confidence: 62%
“…Rituximab is an effective remission-inducing agent in GPA. The addition of a conventional maintenance agent to RTX and GCs decreased the incidence of relapse and did not result in a higher incidence of adverse events [24]. Rituximab is generally well tolerated, but side effects include leucopenia and infection.…”
Section: Reumatologia 2015; 53/6mentioning
confidence: 99%